The Inner Functioning of Local Governance Networks in Centralized Countries: A ‘Brave New World’? - Patrícia Silva; Luís F. Mota; Raúl Carneiro; Raquel Valentim; Filipe Teles (Social Sciences, 2023)
Local governance networks are increasingly seen as the big idea to cope with issues that are complex enough in scope and scale to require a diversity of expertise and resources. While conventional narrative has posited that local networks are optimal for addressing a range of policy problems, and enhancing democratic participation, scarce attention has been devoted to understanding their inner working. A relevant gap in the literature pertains to the impact of central government intervention in igniting such arrangements on the diversity of actors, the intensity of interactions among actors, or their coordination practices. Such assessment is particularly relevant in centralized contexts. This article seeks to map and characterize the inner working of local networks in such a context—Portugal. The empirical analysis highlights the crucial role of central government in igniting local networks and in ensuring higher levels of formal intensity of collaboration to reduce transaction costs. Keeping such arrangements under the radar of central government, however, may curtail the diversity of actors, policy areas, and curb stakeholders’ commitment in local governance arrangements.